Waste engine oil as a sustainable approach for asphalt rejuvenation and modification: A review - Raza Mehmood; Fauzan Mohd Jakarni; Ratnasamy Muniandy; Salihudin Hassim; Nik Norsyahariati Nik Daud; Anwaar Hazoor Ansari (Heliyon)
The significant growth in road infrastructure worldwide over the last decade has resulted in a notable increase in the demand for asphalt binder. However, the utilization of asphalt binder in the road industry poses challenges to environmental sustainability and economic standpoints. The application of vehicular loads and exposure to environmental factors throughout the service life of roads contribute to the deterioration of binder properties, such as hardening and aging, ultimately leading to premature road failure. Therefore, researchers have strived to explore further alternative materials to overcome these challenges, to improve the performance of flexible pavements. Waste Engine Oil (WEO) is one such material that has shown promising effects on asphalt binder. This review aims to conduct an in-depth analysis of previous literature to explore the potential utilization of WEO as a modifier and rejuvenator for asphalt binders. WEO effectively rejuvenates aged asphalt binders, however, the required quantity for rejuvenation varies depending on asphalt characteristics. It was found that the inclusion of the WEO as asphalt modifier significantly affects the high-temperature properties of the WEO-modified asphalt binder. Conversely, WEO addition enhances lower temperature properties, improving thermal and fatigue resistance. Furthermore, the compromise properties of WEO-modified asphalt are enhanced by incorporating various additional additives such as lignin, SBS, polyphosphoric acid and crumb rubber. It was revealed that composite modification can partially substitute 8–15 % asphalt binder, which would be a way forward in cost-effective sustainable construction in the pavement industry. However, additional research is necessary to explore futuristic advancements in WEO modification technology.